2001
DOI: 10.1017/s0021859601008656
|View full text |Cite
|
Sign up to set email alerts
|

Optimum plant populations for okra (Abelmoschus esculentus) in a mixture with cassava (Manihot esculenta) and its relevance to rainy season-based cropping systems in south-western Nigeria

Abstract: Experiments were conducted in Nigeria to evaluate the optimum plant population density for okra (Abelmoschus esculentus) sown in monoculture or intercropped with cassava (Manihot esculenta). The crops were sown as late and early season crops in 1997 and 1998. Okra was sown at varied spacings to achieve final plant densities of 25 000, 35 000 and 50 000 plants\ha in both monoculture and mixed stands. Intercropping had no significant effect on okra phenology (time to vegetative growth, flowering and fruiting). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…The interaction effects of N 125 with S 10 , S 15 , S 20 and N 100 with S 20 were at par with N 100 S 15 for single pod weight. [38,24].…”
Section: Single Pod Weight :(G)mentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction effects of N 125 with S 10 , S 15 , S 20 and N 100 with S 20 were at par with N 100 S 15 for single pod weight. [38,24].…”
Section: Single Pod Weight :(G)mentioning
confidence: 99%
“…Since every node has a potential to produce flower which directly influence the yield per plot. [5,17,24]. …”
Section: Total Green Pod Yield :( Q/ha)mentioning
confidence: 99%
“…Moreover, intercropping offers the tropical farmers an early income from the annual vegetable intercrops before the main crop is harvested [22] [23]. [24] observed that annual vegetable crops such as celosia, okra and pepper occupy valuable ecological niche in tropical agriculture and play significant roles in the eco-physiology of mixed systems. Nonetheless, studies on mixed cropping have indicated that intercropping systems despite the reduced individual crop performances of component crops [25] not only produced more overall yield because of more efficient utilization of environmental resources compared to sole cropping [22] [26]- [30], but is also very advantageous in the maintenance of soil fertility through effective soil cover and amelioration of the environment [29]- [32].…”
Section: Introductionmentioning
confidence: 99%
“…The fresh young leaves, stems and young flower spikes are used to produce a nutritious and tasty soup: especially in West Africa. [24] had stated that vegetables such as leafy (celosia and amaranthus) or fruit types (okra and pepper) occupy a valuable ecological niche in tropical agriculture and play significant roles in the eco-physiology of mixed systems. Moreover, celosia competes better with weeds and tolerates dry soil better than other vegetable crops and also it responds well to nutrients or fertilizer (organic).…”
Section: Introductionmentioning
confidence: 99%
“…Although differences in fresh pod yield for cassava Odongbo/okra intercrop were not significantly greater than for okra monoculture, these results indicate that intercropping with cassava did not markedly affect the phenology of okra irrespective of sowing date and cropping season. Earlier studies (Ikeorgu et al, 1989;Olasantan, 1999Olasantan, , 2001b have reported good performance of okra intercropped with cassava as a result of improved soil micro-environment, reductions (22-30%) in weed competition and in the number of root-gall okra plant Ϫ1 over monoculture. Hulugalle and Ezumah (1991) …”
Section: Effect Of Cropping System On Okramentioning
confidence: 96%